PELAKSANAAN BAURAN PROMOSI AIR TERJUN AEK MARTUA OLEH DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN ROKAN HULU PADA MASA COVID-19 - Hujaimah Daulay; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the tourism promotion strategy that has been implemented by the Department of Tourism and Culture of Rokan Hulu Regency to determine the inhibiting factors of the promotional activities carried out. The research method used is descriptive qualitative. The main informant of the research is the Head of Marketing at the Rokan Hulu Regency Tourism Office. Supporting informants are the Destinations Division of the Tourism and Culture Office of Rokan Hulu Regency. Data collection was carried out by direct observation, interviews and documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation and conclusion drawing. The results of this study concluded that the tourism promotion mix has been implemented by the Department of Tourism and Culture of Rokan Hulu Regency, namely advertising (Advertising), sales promotion, and public relations. In addition, the inhibiting factor for promotion is the local community who does not want to cooperate with the Tourism and Culture Office of Rokan Hulu Regency, accommodation such as roads that are still very limited and cannot be passed by cars, management and human resources are still lacking causing the Department of Tourism and Culture to find it difficult to carry out promotional activities. Keywords: promotion mix, promotion strategy, tourism